Multiple Methane Activation Pathways on Ga‐modified ZSM‐5 Zeolites Revealed by Solid‐State NMR Spectroscopy. Issue 15 (18th June 2020) - Zhao, Xingling; Xu, Jun; Chu, Yueying; Qi, Guodong; Wang, Qiang; Gao, Wei; Li, Shenhui; Feng, Ningdong; Deng, Feng
Abstract: Methane activation on Ga‐modified ZSM‐5 zeolites (Ga/ZSM‐5) was studied by solid‐state NMR spectroscopy. Two types of Ga species, namely highly dispersed oxides and cationic Ga species, were determined by 71 Ga QCPMG NMR. The activation of methane on Ga/ZSM‐5 was explored by using 13 C and 1 H MAS NMR. Four types of Ga‐CH3 species along with Ga‐OH groups were observed on Ga/ZSM‐5, evidencing different pathways for heterolytic cleavage of C−H bond of methane. Two‐dimensional (2D) 1 H‐ 1 H correlation NMR experiments provide detailed information on the location and local environment of the Ga‐CH3 species by correlating the protons in Ga‐CH3 with those in Ga‐OH and other hydroxyls on zeolite. The structures of different Ga‐CH3 species were further determined by 2D 1 H‐ 13 C heteronuclear correlation NMR experiments, which were supported by theoretical calculations. The activation routes of C−H bond in methane were proposed on Ga/ZSM‐5 zeolite. Abstract : Methane activation : Different types of Ga‐CH3 species were observed in methane activation on Ga‐modified ZSM‐5 zeolite, evidencing different pathways for heterolytic cleavage of C−H bond of methane. Two‐dimensional solid‐state NMR experiments provided detailed information on the location and local environment of the Ga‐CH3 species.